Manhattan Cocktails Danses Concertantes returns to Sadler's Wells - Parry, Jann (Dance Books Ltd., Alton,Hampshire (UK), 2004)
Danses Concertantes returns to Sadler's Wells. In Christopher Wheeldon's Liturgy, Wendy Whelan and Jock Soto are two figures picked out in light like twin souls. PALABRAS CLAVE: Christopher Wheeldon, Danses Concertantes, Liturgy, Variations pour une porte et un soupir, Hallelujah Junction.